Aurora - Robson, Mark, 1966- (London : Simon and Schuster, 2009)
Dragonriders Elian, Kira, Nolita, and Pell, having obtained the third of the four orbs needed to restore the Oracle, are drawn into a huge aerial battle between all the dragon enclaves with the fate of dragonkind hanging in the balance.
6.1
3-6
3-6
Keywords: Dragons -- Juvenile fiction; Dragons -- Fiction; Fantasy; Dragons -- Fiction; Fantastic fiction; Fantastic fiction